Statistical thermodynamics - Schrödinger, Erwin, 1887-1961 (Dover Publications, 1965)
Nobel laureate's brilliant attempt to develop a simple, unified standard method of dealing with all cases of statistical thermodynamics (classical, quantum, Bose-Einstein, Fermi-Dirac, etc.). Discussions of Nernst theorem, Planck's oscillator, fluctuations, the n-particle problem, problem of radiation, much more. *** This book is an excellent guide in statistical thermodynamics. It's started with the theoretical justification of phenomenological thermodynamics and its system of concepts. In principle the methods of statistical mechanics are applicable to non-equilibrium states as well as to equilibrium properties. The author (Nobel prize,1933) treats only the theory of equilibrium properties for which the destination "Statistical Thermodynamics" has been adopted. As a consequence of the structure of phenomenological thermodynamic, statistical thermodynamics developed in this book separates into two principal parts: the derivation of thermodynamic principles and the calculation of thermodynamic functions for concrete systems. This text seems especially good for teaching basic thermodynamics and statistical mechanics. I recommend this book especially for students, because it's highest quality is the clarity of the exposed physical ideas.